2019
DOI: 10.1155/2019/2761041
|View full text |Cite
|
Sign up to set email alerts
|

Morinda citrifolia and Its Active Principle Scopoletin Mitigate Protein Aggregation and Neuronal Apoptosis through Augmenting the DJ-1/Nrf2/ARE Signaling Pathway

Abstract: Given the role of oxidative stress in PD pathogenesis and off-target side effects of currently available drugs, several natural phytochemicals seem to be promising in the management of PD. Here, we tested the hypothesis that scopoletin, an active principle obtained from Morinda citrifolia (MC), efficiently quenches oxidative stress through DJ-1/Nrf2 signaling and ameliorates rotenone-induced PD. Despite reducing oxidative stress, the administration of MC extract (MCE) has lessened protein aggregation as eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 42 publications
0
24
0
3
Order By: Relevance
“…Scopoletin suppressed the formation of advanced glycation end products (AGEs), hyperglycemia, and insulin resistance and enhanced Nrf2, Akt, and GLUT2 in hepatocytes [121]. Very recently, Narasimhan et al reported that scopoletin protected against oxidative stress and apoptosis induced by rotenone via Nrf2 activation and investigated its neuroprotective effects for Parkinson's disease in a rat model and in vitro using SH-SY5Y cells [122].…”
Section: Urolithin Amentioning
confidence: 99%
“…Scopoletin suppressed the formation of advanced glycation end products (AGEs), hyperglycemia, and insulin resistance and enhanced Nrf2, Akt, and GLUT2 in hepatocytes [121]. Very recently, Narasimhan et al reported that scopoletin protected against oxidative stress and apoptosis induced by rotenone via Nrf2 activation and investigated its neuroprotective effects for Parkinson's disease in a rat model and in vitro using SH-SY5Y cells [122].…”
Section: Urolithin Amentioning
confidence: 99%
“…Thus, it is possible that oxidation of Cys106 may act as the signal for DJ-1 to prevent mitochondrial dysfunction during ROS production in PD. In addition, DJ-1 regulates the expression of antioxidant genes by promoting nuclear translocation of Nrf2, a transcription factor that binds to genes containing an antioxidant response element (ARE) [ 41 , 47 ].…”
Section: Oxidative Stress and Park Genesmentioning
confidence: 99%
“…Additionally, biological studies in a rodent Parkinson’s disease model system demonstrate the neuroprotective effect of reynosin against dopamine-induced neuronal cell death [ 51 ]. Moreover, scopoletin, also present in extract, is a coumarin present in different species of plants that possess anticancer properties inducing cell cycle arrest and caspase-3 activation in the prostate cancer cell line [ 52 ], while inducing PARP cleavage and DNA fragmentation in promyeloleukemic HL-60 cells which lead to apoptosis [ 53 ]; and is able to enhance the neuronal defense system and protect the brain from rotenone-induced oxidative stress and Parkinson’s disease [ 54 ].…”
Section: Discussionmentioning
confidence: 99%